2024
DOI: 10.3390/electronics13061079
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Accurate Short-Term Load Forecasting with a Hybrid Model

Sang Mun Shin,
Asad Rasheed,
Park Kil-Heum
et al.

Abstract: Short-term electric load forecasting (STLF) plays a pivotal role in modern power system management, bolstering forecasting accuracy and efficiency. This enhancement assists power utilities in formulating robust operational strategies, consequently fostering economic and social advantages within the systems. Existing methods employed for STLF either exhibit poor forecasting performance or require longer computational time. To address these challenges, this paper introduces a hybrid learning approach comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Short-term load forecasting (STLF) is useful for utilities in predicting energy demand during peak hours and preparing for potential supply shortages. Additionally, it assists electricity market participants in managing energy trading activities and mitigating risks arising from sudden fluctuations in demand or supply [4]. It was observed that 80% of the electrical energy demand forecasting concerned STLF, while MTLF and LTLF accounted for 15% and 5%, respectively.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Short-term load forecasting (STLF) is useful for utilities in predicting energy demand during peak hours and preparing for potential supply shortages. Additionally, it assists electricity market participants in managing energy trading activities and mitigating risks arising from sudden fluctuations in demand or supply [4]. It was observed that 80% of the electrical energy demand forecasting concerned STLF, while MTLF and LTLF accounted for 15% and 5%, respectively.…”
Section: Introduction 1backgroundmentioning
confidence: 99%